Epigenetic modification in liver fibrosis: Promising therapeutic direction with significant challenges ahead - Runping Liu; Yajing Li; Qi Zheng; Mingning Ding; Huiping Zhou; Xiaojiaoyang Li (Elsevier, 2024)
Liver fibrosis, characterized by scar tissue formation, can ultimately result in liver failure. It's a major cause of morbidity and mortality globally, often associated with chronic liver diseases like hepatitis or alcoholic and non-alcoholic fatty liver diseases. However, current treatment options are limited, highlighting the urgent need for the development of new therapies. As a reversible regulatory mechanism, epigenetic modification is implicated in many biological processes, including liver fibrosis. Exploring the epigenetic mechanisms involved in liver fibrosis could provide valuable insights into developing new treatments for chronic liver diseases, although the current evidence is still controversial. This review provides a comprehensive summary of the regulatory mechanisms and critical targets of epigenetic modifications, including DNA methylation, histone modification, and RNA modification, in liver fibrotic diseases. The potential cooperation of different epigenetic modifications in promoting fibrogenesis was also highlighted. Finally, available agonists or inhibitors regulating these epigenetic mechanisms and their potential application in preventing liver fibrosis were discussed. In summary, elucidating specific druggable epigenetic targets and developing more selective and specific candidate medicines may represent a promising approach with bright prospects for the treatment of chronic liver diseases.